2020
DOI: 10.1002/jts.22508
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Impulsivity in the Association Between Posttraumatic Stress Disorder Symptom Severity and Substance Use in Male Military Veterans

Abstract: High rates of posttraumatic stress disorder (PTSD) and comorbid substance use disorder (SUD) are prevalent in military veterans. However, few studies have investigated impulsivity as a risk factor for engaging in substance use behavior for individuals who are experiencing PTSD symptoms. The present study evaluated impulsivity as a moderator of the association between PTSD symptoms and alcohol/drug use. Male military veterans (N = 106) completed self‐report measures of alcohol use behavior, drug use behavior, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“…In a recent study of 145 patients with EDs, those with alcohol and drug abuse symptoms represented a specific phenotype characterized by greater impulsive personality, emotion dysregulation, and problems with executive functioning [ 103 ]. Among male military veterans ( n = 106), impulsivity moderated the relationship between PTSD symptoms and alcohol consumption [ 104 ], with relevance discussed in more detail below. In addition to higher levels of impulsivity, individuals with FA are more likely to report a family history of addiction [ 105 ] which may be consistent with genetic underpinnings.…”
Section: Substance Use Disordersmentioning
confidence: 99%
“…In a recent study of 145 patients with EDs, those with alcohol and drug abuse symptoms represented a specific phenotype characterized by greater impulsive personality, emotion dysregulation, and problems with executive functioning [ 103 ]. Among male military veterans ( n = 106), impulsivity moderated the relationship between PTSD symptoms and alcohol consumption [ 104 ], with relevance discussed in more detail below. In addition to higher levels of impulsivity, individuals with FA are more likely to report a family history of addiction [ 105 ] which may be consistent with genetic underpinnings.…”
Section: Substance Use Disordersmentioning
confidence: 99%
“…One point that must not be forgotten here is that past research has also identified impulsivity as a mediator of the PTSD–substance use relationship (Mahoney et al, 2020; Morris et al, 2020). A novel finding here is that the inclusion of risk-seeking as a concurrent mediator seemingly attenuates this relationship to some degree due to collinearity.…”
Section: Discussionmentioning
confidence: 98%
“…As impulsivity is symptomatic of the disorder, it would seem that this construct may be a particularly salient mediator of the PTSD–polydrug use relationship because of research indicating that impulsivity is a risk factor for drug use (Hentges et al, 2018; Kozak et al, 2019; Oshri et al, 2018). Indeed, past research has found impulsivity helps to explain the PTSD–substance use relationship (Mahoney et al, 2020; Morris et al, 2020). However, there is a dearth of research that has sought to delineate self-control into the dual systems concepts.…”
Section: Introductionmentioning
confidence: 99%
“…Behavioral impulsivity is a multifaceted personality disposition related to deficient emotional or behavioral self-control in everyday life decisions (Duckworth and Kern, 2011;Whiteside and Lynam, 2001), whereas inhibitory control represents the ability to override impulses to accomplish a goal-directed task (Sadeh et al 2015). Behavioral impulsivity is consistently related to higher alcohol use (e.g., in Veterans with PTSD symptoms, see Mahoney et al 2020) and several aspects of behavioral impulsivity could also play a role in maintaining PTSD symptoms, such as difficulty with emotional regulation and a propensity towards risky behavior (a PTSD diagnostic item in the DSM-5). Additionally, PTSD symptoms such as hyperarousal could further contribute to aspects of behavioral impulsivity, especially through negative urgency, or the tendency to act impulsively under negative affect (Roley et al 2017).…”
Section: Running Head: Inhibitory Control and Alcohol Predict Ptsd Ch...mentioning
confidence: 99%